SMOKE EXPOSURE AND OCCUPATIONAL RELATED WITH LUNG FUNCTIONAL CAPACITY IN COASTAL COMMUNITIES - I Putu Sudayasa; Indra Dika Pratama; Amiruddin Eso (Universitas Muhammadiyah Semarang, 2017)
Fish curing industry is generally an informal industry that is managed by the community. Regulations on health and safety protection of the workforce and the surrounding communities have received less attention. This study aims to determine the association of smoke exposure and occupation with pulmonary function capacity in coastal communities Lalonggasumeeto village. This research was ananalytic observational with cross sectional study. The sample size were 118 samples with consecutive sampling techniques. Data analysis was performed using chi-square test. This study found that respondents with exposure to smoke less then and until 8 hours/day was (52.5%) and respondents with exposure to smoke more than 8 hours/day was (47.5%). Respondents work as fish fumigation as much as 50%. Respondents with normal pulmonary function capacity was (46.6%) and respondents with abnormal pulmonary function capacity found (53.4%). The analytic results showed, that were smoke exposure and occupation (p-value = 0.000), associated with lung functional capacity. These result conclude that there were association of smoke exposure and occupation with pulmonary function capacity in coastal communities. Sugested, the workers should using personal protective equipment when performing fish fumigation and home ventilations were not adjacent to the fumigation place. Keywords: lung capacity, pulmonary function, smoke exposure, coastal communities, occupation